Elaboración de un manual de procesos y procedimientos de manufacturación, de señalética para el laboratorio de interpretación turística de la unidad académica de ciencias agropecuarias y recursos naturales de la Universidad Técnica de Cotopaxi - Cando Toaquiza, Miguel Ángel (2016)
This research work was carried out based on the manual MINTUR signage and methodology The focus and its contents as is the development of Process and Procedures Manual for the area of signage Building Alternatives Tourist Interpretation Laboratory for Engineering Degree in Ecotourism Technical University of Cotopaxi stands. The document shows the objective consolidation for the implementation and enforcement of their content based on what it will take place depending on the circumstances and the need of the place where it will be applied as is the implementation of tourist signage and maps of thematic location between others) PROGRAM AND TOURIST MARKET generally either cities, (museums, churches, parks, institutions) tract (neighborhoods, parishes, communities, provinces and attractive among others).